2021
DOI: 10.1039/d1sc03743a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoreduction of water catalyzed by a cucurbit[8]uril-secured platinum dimer

Abstract: The cucurbit[8]uril macrocycle can secure a platinum terpyridyl complex into a particularly reactive dimer that catalyzes the photoreduction of water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…Q­[ n ]­s as classical macrocyclic hosts distinguish themselves from other artificial organic macrocycles for fabricating smart supramolecular organic luminescent emissions in recent years, due to the tunable macrocyclic-confinement effect from the confined rigid molecular spaces with different sizes. Generally, the characterization of Q­[ n ]-based supramolecular organic emissions with the size-dependent confinement effect can be classified by the following: (1) The rigid confined cavity and the carbonyl oxygen atoms at the rim of the polar Q­[ n ] portal can efficiently change the electron density distribution or charge transfer of the dye guest molecules. In particular, they can switch the luminescence properties of the dye molecule simply and efficiently through multiple noncovalent interactions without the need for complicated organic synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Q­[ n ]­s as classical macrocyclic hosts distinguish themselves from other artificial organic macrocycles for fabricating smart supramolecular organic luminescent emissions in recent years, due to the tunable macrocyclic-confinement effect from the confined rigid molecular spaces with different sizes. Generally, the characterization of Q­[ n ]-based supramolecular organic emissions with the size-dependent confinement effect can be classified by the following: (1) The rigid confined cavity and the carbonyl oxygen atoms at the rim of the polar Q­[ n ] portal can efficiently change the electron density distribution or charge transfer of the dye guest molecules. In particular, they can switch the luminescence properties of the dye molecule simply and efficiently through multiple noncovalent interactions without the need for complicated organic synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Li and his co‐workers designed and synthesized a 1,3,5‐triphenylbenzene derivative bearing three hydrophilic groups and constructed a stable periodic honeycomb 2D framework through Q[8] and guest in a 2 : 3 molar ratio [14] . All of the above illustrate the incomparable advantages of Q[10] and Q[8] with large cavities in the construction of more diverse and more interesting supramolecular assemblies including covalent dimers, trimers, oligomers of controlled size, honeycomb 2D polymers, or large 3D nanocapsules [15–26] …”
Section: Introductionmentioning
confidence: 99%
“…[14] All of the above illustrate the incomparable advantages of Q [10] and Q [8] with large cavities in the construction of more diverse and more interesting supramolecular assemblies including covalent dimers, trimers, oligomers of controlled size, honeycomb 2D polymers, or large 3D nanocapsules. [15][16][17][18][19][20][21][22][23][24][25][26] In addition, these interesting multivariate supramolecular assemblies demonstrate unique physicochemical properties such as conformational control and fluorescence control. [27][28][29][30] For example, Ni's group used oligo(p-phenylenevinylene) (OPV) as the parent molecule to involve a series of compounds, systematically studied the interaction between OPV derivatives and different Q[n]s, [31][32][33] and found that OPV derivatives with a two-carbon carboxyl chain can construct a white light emission liquid with Q [8] in a specific ratio, which breaks through the limitations of traditional white light materials that require multiple dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Q[8]@G1 2 @Tb 3+ not only effectively induces a unique metallic luminescence but also exhibits specific responses to antibiotics. Masson and co-workers fabricated a Q[8]-based supramolecular photosensitizer and hydrogen-evolving catalyst with a platinum terpyridyl chloride dimer, which was further applied to the photoreduction of water. Compared to Q[6], Q[7], and Q[8], the huge cavity of Q[10] has the significant advantage of encapsulating guest molecules with larger molecular sizes, which helps to expand more abundant orthogonal assemblies. The classical metallo-ligand tripyridine with a huge molecular size is one of the specific guest molecules for Q[10] and can only interact with Q[10] in a host–guest interaction among the many other Q­[ n ]­s. , Liu et al not only confirmed the host–guest interaction of Q[10] with 2 mol tripyridines employing single-crystal X-ray diffraction but also found that a stable complex could be formed even when the tripyridine was coordinated, where Q[10] could also effectively promote the metal–metal interactions between Pt 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Q[8]@G1 2 @Tb 3+ not only effectively induces a unique metallic luminescence but also exhibits specific responses to antibiotics. Masson and coworkers 22 fabricated a Q [8]-based supramolecular photosensitizer and hydrogen-evolving catalyst with a platinum terpyridyl chloride dimer, which was further applied to the photoreduction of water. Compared to Q [6], Q [7], and Q [8], the huge cavity of Q [10] has the significant advantage of encapsulating guest molecules with larger molecular sizes, which helps to expand more abundant orthogonal assemblies.…”
Section: ■ Introductionmentioning
confidence: 99%